Librarians collaborating to teach evidence-based practice: exploring partnerships with professional organizations - Dhakal, Kerry (J Med Libr Assoc, 2018)
OBJECTIVE: The study sought to determine if librarians are collaborating with nurses and professional nursing organizations to teach evidence-based practice (EBP) continuing education courses, workshop, classes, or other training activities. METHODS: A 15-question survey was sent to 1,845 members of the Medical Library Association through email. RESULTS: The survey was completed by 201 consenting respondents. Some respondents (37) reported having experience teaching continuing education in collaboration with professional health care organizations and 8 respondents, more specifically, reported having experience teaching EBP continuing education courses, workshops, classes, or other training activities in collaboration with professional nursing organizations. CONCLUSIONS: The survey results demonstrate that librarians are teaching continuing education classes or workshops in collaboration with professional health care organizations and reveal that there are a small number of librarians collaborating with professional nursing organizations to teach EBP continuing education courses, workshops, classes, or other training activities.